Biophysical and socio-economic synthesis of the effectiveness of land restoration efforts in Kenya - CGIAR Research Program on Water, Land and Ecosystems (2018)
This work was geared for the counties of Bungoma, Siaya and Kakamega. However, areas around the Tana watershed are likely to benefit from similar strategies given the profile of partners.